Amoebic Cerebral Abscess: Still A Diagnostic Dilemma with Fatal Outcome - Jindal, Akriti; Tyagi, Ruchita; Garg, Avantika; Kaur, Gursheen; Chaudhary, Ashwani Kumar; Singh, Gagandeep; Kaur, Harpreet; Sood, Neena (Annals of Pathology and Laboratory Medicine, 2019)
Amoebiasis is defined as infection with Entamoeba histolytica, which enters the body through feco – oral route after consumption of food or water contaminated by cysts. We present a rare case of amoebic brain abscess in a 45 years old patient who came with headache, fever and right sided weakness for 15 days. He was emperically being treated for tuberculosis. As Entamoeba was not suspected, no serological or microbiological investigations for the same were done. Histopathological examination of abscess sent after frontal lobectomy revealed trophozoites of Entamoeba histolytica. Demonstration of trophozoites of Entamoeba on histopathology sections was a surprising finding which clinched the diagnosis in this case. Amoebic brain abscess should be considered as differential diagnosis in all patients who present with signs & symptoms of central nervous system involvement in endemic areas. Early diagnosis and aggressive management with metronidazole is imperative to limit the morbidity and prevent the mortality.